A general spin-complete spin-flip configuration interaction method. Issue 4 (10th January 2018) - Mato, Joani; Gordon, Mark S.
Abstract : A new spin-complete spin-flip configuration interaction (SF-CI) method was developed using the ORMAS-CI algorithm, along with a perturbative correction for capturing dynamic and non-dynamic correlation. Abstract : A new, general spin-correct spin-flip configuration interaction (SF-CI) method is introduced by extending the occupation restricted multiple active spaces (ORMAS) CI method in GAMESS. SF-ORMAS is a single reference CI method that utilizes a high-spin restricted open shell determinant on which an arbitrary amount of spin-flipped excitations are carried out to generate a wave function of desired multiplicity. Furthermore, the SF-ORMAS method allows for a flexible design of the active space(s) to fit the chemical problem at hand. Therefore, a variety of spin-flip schemes can be implemented within this one formalism. As SF-ORMAS mostly accounts for static correlation, dynamic correlation is included through perturbation theory. The new method is demonstrated for single and multiple bond breaking, diradical systems, vertical excitations of linear alkenes, and the singlet–triplet energy gap of silicon trimer.